Integrative taxonomy of the Amazonian red-sided opossum Monodelphis glirina (J.A. Wagner, 1842) (Didelphimorphia: Didelphidae) - Bezerra, Alexandra M. R.; Caramaschi, Fabiana P.; Bonvicino, Cibele R.; Castiglia, Riccardo (Zootaxa, 2018)
New records for Monodelphis glirina, a short-tailed opossum distributed throughout the Amazon region, from Humaitá, Amazonas state, and Confresa, Mato Grosso state, prompted new insights into the geographic distribution and genetic diversity of this species. One of the records extends the species range circa 350 km beyond the previous southeastern limit. Voucher specimens had their identification confirmed by morphological comparison with the holotype and corroborated by molecular data (mitochondrial gene Cytochrome b). Our analyses revealed an east-west geographic structure into two clades that could represent distinct species, M. glirina and M. maraxina. Furthermore, examination of the holotype brought to light that it was never formally linked with the voucher specimen collected by Johann Natterer.